Software development team composition: Personality types of programmer and complex network - Gilal, Abdul Rehman; Omar, Mazni; Jaafar, Jafreezal; Mohd Sharif, Kamal Imran; Mahessar, Abdul Waheed; Basri, Shuib (2017)
Several authors have identified the different personality types for software team composition. Effective personality types for software development roles is still a question.This study aims to measure the relationship between different personality types by using complex network approach for finding effective nodes of personality type for software programmer.In order to achieve the objective, the study was conducted on student population. Myer-Briggs Type Indicator (MBTI) personality assessment tool was used to obtain the personality types of participants. Furthermore, degree centrality, betweenness centrality, and closeness centrality measures were used on data. These measures were used to find the strongly liked personality types among team members, personality types that can create effective communication, and personality types which can work close with other personality types. Basically, two types of results were obtained from applied measures: personality types which are weighted and frequent and personality types which are weak and less frequent.For example, ISTJ, INFJ, ISTP, and INFP personality types were found very less lucrative in working close with other personality types.On the other hand, ISTJ has been found very effective personality type for programmer role in software development literature. The results suggest that each personality type has its own complex behavior which should be extracted for better outcomes. Deciding one particular personality type for programmer role would be an injustice with it. Therefore, this paper recommends to use complex network phenomenon to extract the hidden facts behind each personality types for software development roles.